Evaluation of Drug Storage System in Boyolali Regency Pharmacies According to The Regulation of The Minister of Health of The Republic of Indonesia No 73 of 2016 - Afidatus Sholikah; Eka Wisnu Kusuma (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Drug storage is an important factor in maintaining drug quality so that the quality of drugs remains in accordance with the storage parameters according to Ministry of Health Regulation No. 73 of 2016. This study aims to examine the percentage of compliance with the drug storage system in pharmacies in Boyolali Regency, as regulated in Minister of Health Regulation No. 73 of 2016. The research method used was descriptive observational with data collection using a checklist, observation of pharmacies in Boyolali Regency, and interviews with the pharmacists in charge. Drug storage based on Minister of Health Regulation No. 73 of 2016 shows that storage parameters in 56 pharmacies in 18 subdistricts indicate drug storage system parameters based on dosage form, drug stability temperature, storage equipped with shelves or pallets, air conditioning and refrigerators, therapeutic or pharmacological class, and alphabetical order, showing a compliance rate of 100%. Storage based on the original packaging from the manufacturer showed a compliance rate of 94.42%. Storage areas should not be used to store other items, with a compliance rate of 98.21%, and storage of narcotic and psychotropic drugs showed a compliance rate of 92.86%. The storage systems at 56 pharmacies have met the standards set by the Indonesian Ministry of Health Regulation No. 73 of 2016